2019
DOI: 10.1055/s-0039-1685205
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Treatment Trends of Distal Radius Fractures across Multiple Age Groups

Abstract: Background The purpose of this study is to assess the epidemiology, population-specific treatment trends, and complications of distal radius fractures in the United States. Methods The PearlDiver database (Humana [2007–2014], Medicare [2005–2014]) was used to access US inpatient and outpatient data for all patients who had undergone operative and nonoperative treatment for a distal radius fracture in the United States. Epidemiologic analysis was performed followed by age-based stratification, to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
73
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 39 publications
10
73
0
2
Order By: Relevance
“…Of all DRFs treated surgically as the primary treatment, more than four out of five underwent internal plate fixation. This is in accordance with previous studies, which have reported that plate fixation has become the predominantly preferred surgical method in recent years in several countries [4,11,18,29,30].…”
Section: Primary Treatmentsupporting
confidence: 93%
See 3 more Smart Citations
“…Of all DRFs treated surgically as the primary treatment, more than four out of five underwent internal plate fixation. This is in accordance with previous studies, which have reported that plate fixation has become the predominantly preferred surgical method in recent years in several countries [4,11,18,29,30].…”
Section: Primary Treatmentsupporting
confidence: 93%
“…Distal radius fractures (DRFs) are the most common orthopaedic fractures in the western world [1]. The distribution of DRFs in the general population is bimodal with incidence peaks in young men and in postmenopausal women [1][2][3][4]. DRFs in younger patients with good bone stock are most commonly associated with high-energy trauma [5], while low-energy trauma, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Distal radial fracture is a very common injury, which has shown a bimodal distribution of age-speci c incidence with an increasing prevalence in adults and aging people [1][2][3]. Non-surgical treatment is generally adopted for non-or minimally displaced fractures.…”
Section: Introductionmentioning
confidence: 99%